The Influence of Toxic Leadership, Work Conflicts and Work Situations on Employee Performance through Employee Satisfaction at the Job Training Center East Java Province - Arifin, Zaenal; Riyadi, Slamet; Sumiati , Sumiati (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
UPT East Java Job Training Center is one of the organizations engaged in job training services which has recently emerged many competitors in this field. This BLK must improve its performance so that it can still compete with its competitors. Currently, workers are required to adapt quickly to changes and have high skills and creativity to compete with other workers. This is in line with the goal of the UPT Job Training Center, which is to contribute to improving workforce competence through the implementation of competency-based training. The problem that still arises in the company is that the level of employee performance is not optimal because the leadership has not been on the side of employees, although the company has tried to improve employee performance through various programs such as improving incentives, creating good and comfortable working conditions or situations as much as possible, but employee performance still does not meet expectations. The purpose of this study is to determine the influence of toxic leadership, work conflicts and work situations on employee performance through employee satisfaction at the East Java Job Training Center. This study uses a quantitative method with primary data sources obtained from the distribution of questionnaires. The population of this study is all employees in BLK East Java, which is as many as 90 employees.  Using the saturated sampling method, which is included in non-probability sampling. The data analysis method uses descriptive analysis and SEM-PLS analysis. The results of the study showed that toxic leadership variables, work conflicts and work situations had a positive and significant effect on employee performance through employee satisfaction at the East Java Job Training Center.